Evaluation and stages of surgical innovations. - Barkun, J; Aronson, J; Feldman, L; Maddern, G; Strasberg, S; Altman, D; Barkun, J; Blazeby, J; Boutron, I; Campbell, W; Clavien, P; Cook, J; et al. (2009)
Surgical innovation is an important part of surgical practice. Its assessment is complex because of idiosyncrasies related to surgical practice, but necessary so that introduction and adoption of surgical innovations can derive from evidence-based principles rather than trial and error. A regulatory framework is also desirable to protect patients against the potential harms of any novel procedure. In this first of three Series papers on surgical innovation and evaluation, we propose a five-stage paradigm to describe the development of innovative surgical procedures.